High Rate of Drug‐Free Remission After Induction Therapy With Golimumab in Early Peripheral Spondyloarthritis. Issue 11 (26th October 2018) - Carron, Philippe; Varkas, Gaëlle; Renson, Thomas; Colman, Roos; Elewaut, Dirk; Van den Bosch, Filip
Abstract : Objective: New treatment algorithms using tumor necrosis factor (TNF) blockers in early stages of spondyloarthritis (SpA) induce high rates of clinical remission or low disease activity. It could be anticipated that such early intervention strategies in peripheral SpA may induce drug‐free remission. We undertook this study to evaluate drug‐free clinical remission after induction therapy with golimumab in patients with very early active peripheral SpA, and to identify patient characteristics that predict sustained drug‐free remission. Methods: Eligible patients were age ≥18 years and fulfilled the Assessment of SpondyloArthritis international Society criteria for peripheral SpA. All patients had symptom duration of <12 weeks. Sustained clinical remission was defined as the absence of arthritis, enthesitis, and dactylitis at 2 consecutive major visits, after which treatment was withdrawn. Patients were prospectively followed up to assess the rate of sustained drug‐free clinical remission and clinical relapse. Results: Eighty‐two percent of patients (49 of 60) fulfilled sustained clinical remission criteria after a regimen of induction therapy with golimumab. The majority of patients already reached this status at week 24 (n = 30), with an additional 11 and 8 patients at weeks 36 and 48, respectively. All patients had a follow‐up period of at least 18 months after drug withdrawal. Fifty‐three percent of patients (26 of 49) still have drug‐free remission of their disease. Inability to sustain drug‐free remission was associated with the presence of psoriasis and polyarticular disease (swollen joint count >5). Conclusion: Anti‐TNF treatment in very early peripheral SpA results in a remarkably high rate of sustained clinical remission. More than 50% of patients continue to have remission of their disease after withdrawal of therapy, which highlights a defined window of opportunity permitting induction of drug‐free remission.